Application of Design Thinking as a Renewable Pastoral Method in Faith Formation Based on Age And Sustainable in The Faith of The Alpha Generation - Cindy Fransiska Br Tarigan (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2024)
This research aims to explore and analyze the positive influence of implementing Faith Formation based on age groups and sustainability (Formatio Iman Berjenjang dan Berkelanjutan) by applying design thinking as a pastoral method on the faith formation of Alpha Generation children. Faith formation based on age groups and sustainable as the pastoral focus of the Archdiocese of Semarang aims to form Catholics who believe in an intelligent, resilient, missionary and dialogical way that leads to information (knowledge), formation (formation), and transformation (change to be more faithful to achieve the perfection of the Christian life). The Design Thinking method is useful for designing creative and innovative implementation strategies according to the age level and needs of Alpha generation children. The research applies qualitative research methods through observation and interviews with children who join the Children's Faith Assistance (PIA), facilitators, parents, and parish priests to see the experience and application of FIBB with the Design Thinking approach for children. Based on the results of observations and data collection, FIBB with a design thinking approach has worked very well and can answer the needs of the people, for example, the implementation of Children's Catechesis which is held in the smallest unit of the parish and Catholic Parenting. Both mentoring programs are a form of innovative faith formation design that is based on the specific needs of the community. Through the design thinking approach created in coordination with FIBB, children's attendance in Children's Faith Development and donations for them have increased significantly